BETWEEN LIKING AND DISLIKING STUDENTS: A TEACHER’S INNOVATION - Nabila Muna Mufidah; Aramudin (Universitas Islam Negeri Mataram, 2025)
Social Studies (IPS) learning at the elementary school level often faces challenges related tolow student interest and engagement, leading to the phenomenon of “learning dislike.” This ismainly due to less innovative, monotonous teaching methods. This study aims to examinehow teachers apply innovative strategies to avoid this phenomenon and increase studentinterest in IPS lessons. Using a qualitative case-study Design, this study involved SSE teachersand students at SDIT Fadhilah. Data were collected through in-depth interviews, participatoryobservation, and documentation, which were then analyzed using thematic analysis. Theprimary focus of this study was on the application of project-based learning (PjBL) andproblem-based learning (PBL) methods, as well as the use of technology to support thelearning process. The findings of this study indicate that these methods can reduce students’disinterest in the subject and increase their engagement in social studies learning. However,challenges related to time constraints and access to technology need to be addressed in theimplementation of these innovative strategies. This study is expected to provide insights intodeveloping more engaging and relevant learning experiences for students at SDIT Fadhilahand other elementary schools.